The sexual health Y reproductive of the students of level preparatory: a frame of analysis for the intervention of Nursing on the community - García Madrid, Guillermina; Moreno Tochihuitl, Maricarmen; Cruz Rivera, Carmen; Antonio Ramos Vázquez, Jorge; Laura Méndez Ovando, María; Ortiz Ramírez, Gisela; de León Gómez, Alí (Seven Editora, 2023)
The teachers of the Department of Education in Community Nursing of the Faculty of Nursing of the Benemérita Autonomous University of Puebla, Mexico and of the Community Centers of Attention to Life Care (CECACVI - BUAP), in the development of the program "Care of the sexual and reproductive health of university students "(CUSASEX, 2012), implemented since 2006 in schools of various educational levels, the Faculty of Nursing and the university itself, identified sexual and reproductive knowledge, behaviors and practices in students of a public preparatory school, to have a diagnosis that will guide the preventive interventions to be carried out in the "Take care of your health" day. The study was descriptive, correlational, cross-sectional, carried out in 318 students selected at random. Of the surveyed population, 35.9% have an active sexual life (VSA), 21.6% started it between 12 and 13 years of age and 78.4% between 14 and 17 years of age. Of those who have VSA, only 40.8% use a condom, although 87.0% reported having received information about this means of protection from their parents at home and health professionals at school. There was no relationship between age and gender with the practice of safe and protected sex (r = .213, p = .187; r = 0.50, p = .758), but with having received information (r = .362, p = .022). The results obtained showed a high exposure to the risk of sexually transmitted diseases and unwanted pregnancies on the part of the students, for which interventions were implemented aimed at limiting the risk, strengthening safe and protected sex, and the co- responsibility of the students in the health care and the LGAC of the Academic Body of Community Nursing called "Community Care: From the Nursing Perspective". DOI: 10.56238/pacfdnsv1-128